2015
DOI: 10.1002/ajhb.22763
|View full text |Cite
|
Sign up to set email alerts
|

Sibling effects on nutritional status: Intersections of cooperation and competition across development

Abstract: Closely aged siblings do not always represent competitors. In this ecocultural context, those aged ≥5 years old appear to cooperate to improve their siblings' nutritional status. By evaluating the effects of siblings during specific risk periods, we offer a strategy to untangle the intersections of cooperation and competition. Our results add to the growing body of evidence showing benefits to allocare and further demonstrate that even children target their assistance toward vulnerable periods in development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 57 publications
(88 reference statements)
2
30
0
Order By: Relevance
“…Additional diseases known to be problematic include bronchitis, sexually‐transmitted diseases, and high blood pressure (Hewlett, ). Helfrecht and Meehan () found that fully one‐third of Ngandu children had weight‐for‐age (33.04%) and height‐for‐age (34.51%) z ‐scores 2 SD below CDC reference means, indicating that nutritional stress is relatively high in this population.…”
Section: Introductionmentioning
confidence: 97%
“…Additional diseases known to be problematic include bronchitis, sexually‐transmitted diseases, and high blood pressure (Hewlett, ). Helfrecht and Meehan () found that fully one‐third of Ngandu children had weight‐for‐age (33.04%) and height‐for‐age (34.51%) z ‐scores 2 SD below CDC reference means, indicating that nutritional stress is relatively high in this population.…”
Section: Introductionmentioning
confidence: 97%
“…Standardized anthropometric measurements are a common way to track the health and nutrition of children and adolescents. Standardized height‐for‐age (HAZ) and weight‐for‐age (WAZ) z ‐scores calculated using means from international growth charts (WHO or CDC) reveal the growth of individual children against reference populations (Helfrecht & Meehan, ). These standardized scores are the basis for characterizing child health and determining if children are failing to thrive (Kramer, Veile, & Otárola‐Castillo, ).…”
Section: Introductionmentioning
confidence: 99%
“…These standardized scores are the basis for characterizing child health and determining if children are failing to thrive (Kramer, Veile, & Otárola‐Castillo, ). Across different populations, variation in these anthropometric measures have been linked to sex (Christiaensen & Alderman, ; Sakisaka et al, ), age (Helfrecht & Meehan, ; Kramer et al, ), education (Cochrane, Leslie, & O'Hara, ), and wealth (Barros et al, ; Godoy et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations